Elements of Capacity in Hmong Community-based Organizations - (:unkn) unknown (My University, 2019)
Capacity building efforts in for-profit and non-profit organizations are thought to be positively associated with increasing organizational effectiveness. As a result, organizational capacity research on non-profit organizations continues to expand as federal funding, charitable giving, and private donations decrease or remain stagnant. With less funding opportunities in combination with the increasing number of non-profit organizations and for-profit organizations competing for scarce resources, how to increase organizational capacity is one area of research scholars are pushing for further analysis. This dissertation continues that analysis through a case study of Hmong mutual assistance associations in Wisconsin and asks: What factors hinder the ability of Hmong community-based organizations to meet their goals and objectives? What are the capacity constraints of Hmong community-based organizations? While previous research on organizational capacity focused on larger (e.g. higher total revenue, age, and the number of staff) non-profit organizations, the research on smaller, community-based organizations remains understudied. More specifically, the discourse surrounding the capacity building in non-profits overlooks the ability of smaller organizations to initiate the evaluation process. I argue that the that lack of financial resources coupled with the absence of knowledgeable and skilled human resources in community-based organizations negatively affect their ability to determine where to apply capacity building efforts and develop strategies to increase their capacity. This produces additional hardship in organizations with limited resources seeking to increase their capacity. The goal of this study is to provide an understanding of the current state of Hmong mutual assistance associations and to expand or add to the areas of evaluation in which capacity building efforts might result in the greater sustainability of these agencies and advance the Hmong community.
Keywords: Community-based Organizations; Hmong; Mutual Assistance Associations; Organizational Capacity